The cannabinoid Δ(9)-tetrahydrocannabivarin (THCV) ameliorates insulin sensitivity in two mouse models of obesity - Wargent, E T (Nature Publishing Group, 2013)
BACKGROUND: Cannabinoid type-1 (CB1) receptor inverse agonists improve type 2 diabetes and dyslipidaemia but were discontinued due to adverse psychiatric effects. Δ(9)-Tetrahydrocannabivarin (THCV) is a neutral CB1 antagonist producing hypophagia and body weight reduction in lean mice. We investigated its effects in dietary-induced (DIO) and genetically (ob/ob) obese mice. METHODS: We performed two dose-ranging studies in DIO mice; study 1: 0.3, 1, 2.5, 5 and 12.5 mg kg(−1), oral twice daily for 30 days and study 2: 0.1, 0.5, 2.5 and 12.5 mg kg(−1), oral, once daily for 45 days. One pilot (study 3: 0.3 and 3 mg kg(−1), oral, once daily) and one full dose-ranging (study 4: 0.1, 0.5, 2.5 and 12.5 mg kg(−1), oral, once daily) studies in ob/ob mice for 30 days. The CB1 inverse agonist, AM251, oral, 10 mg kg(−1) once daily or 5 mg kg(−1) twice daily was used as the positive control. Cumulative food and water intake, body weight gain, energy expenditure, glucose and insulin levels (fasting or during oral glucose tolerance tests), plasma high-density lipoprotein and total cholesterol, and liver triglycerides were measured. HL-5 hepatocytes or C(2)C(12) myotubes made insulin-resistant with chronic insulin or palmitic acid were treated with 0, 1, 3 and 10 μℳ THCV or AM251. RESULTS: THCV did not significantly affect food intake or body weight gain in any of the studies, but produced an early and transient increase in energy expenditure. It dose-dependently reduced glucose intolerance in ob/ob mice and improved glucose tolerance and increased insulin sensitivity in DIO mice, without consistently affecting plasma lipids. THCV also restored insulin signalling in insulin-resistant hepatocytes and myotubes. CONCLUSIONS: THCV is a new potential treatment against obesity-associated glucose intolerance with pharmacology different from that of CB1 inverse agonists/antagonists.